Novel low-frequency maternal mosaicism mutation of CHRDL1 gene resulted in the X-linked megalocornea in the offspring - Nguyen, Minh Phu; Nguyen, Khanh Linh; Pham, Quang Anh; Nguyen, Huu Hong Thu; Nguyen, Hai Ha (Vietnam Journal of Biotechnology, 2024)
X-linked megalocornea (MGC1) is an inherited disorder resulting from mutations of the CHRDL1 gene. Common symptoms of megalocornea include oversized cornea, deeper fluid-filled space between the cornea and iris, blurred or distorted vision at every distance, leading to mild vision issues. In this report, we present the first cases of megalocornea caused by the maternal low-frequency somatic mosaicism of the novel CHRDL1 mutation. Two Vietnamese siblings, 5 years old (MG001) and 13 years old (MG002) visited the hospital for regular check-ups with manifestations such as myopic, exophthalmia, and enlarged cornea. They were suspected of having inherited megalocornea disorder without glaucoma symptoms. The DNA genome of the proband (MG001) was applied for whole exome sequencing (WES) analysis, and the result revealed a hemizygous pathogenic variant c.943dupA in the CHRDL1 gene, which results in a frameshift mutation (p.Ile315fs) in protein. This mutation was also identified in the proband (MG002) by Sanger sequencing. Notably, the CHRDL1 c.943dupA mutation was recognized at a very low fraction in the maternal DNA after triplicate Sanger sequencing, indicating that the mother has a mosaicism mutation of CHRDL1 c.943dupA. This study reported a rare case of X-linked megalocornea in a family and provides a novel genetic factor relating to an eye disorder in Vietnam.